(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
When people want to know how many languages other people know, they simply ask what language they speak. They don’t ask what languages they read or write mainly because speaking is predominantly on focus when it comes to learning foreign languages. Subsequently, this makes researchers do more research and find most optimal ways to develop students’ speaking skill. This course of action started several decades ago in ESL and EFL field and have made a considerable progress so far. The researchers identified the phenomenon like complexity, accuracy and fluency based on the interdisciplinary studies. This articles briefly introduces the notions of CAF (complexity, accuracy and fluency) and the history of the progress made in this area while trying to draw conclusions on the sequence of those three subcomponents in teaching foreign languages.